PENGELOLAAN KUALITAS AIR ASAM TAMBANG SETTLING POND PADA KEGIATAN PERTAMBANGAN BATUBARA DI KABUPATEN TANAH LAUT - Anggaita, Dona Rosti; Suyanto, Suyanto; Nugroho, Yusanto; Razie, Fakhrur (EnviroScienteae, 2024)
Management of acid mine drainage is necessary to ensure that the seetlingpond outlet meets the required environmental quality standards. This research was conducted at the seetlingpond location of PT. Jorong Barutama Greston. The aim of this research is to analyze the relationship between the seetlingpond inlet discharge and the use of lime using manual and automatic methods with the outlet parameter sizes being pH Fe, Mn and Cd. Data collection was carried out for approximately 1 year. Observations were taken on a monthly average, both discharge, amount of lime and results of chemical analysis of water quality. The results showed that the method of using lime automatically produces a significant linear relationship between the amount of discharge and the use of lime, while the use of lime manually does not occur consistently between the amount of discharge and the amount of lime so that the use, for the results of water quality analysis either manually or using a lime mixing machine, both produce water quality output that meets environmental quality standards based on the standards of South Kalimantan Governor Regulation No. 36 of 2008.